Fourier-Based Filtering Approach for Identification of Protein-Coding Regions in DNA Sequences - Das, Bihter; Turkoglu, Ibrahim (Ieee, 2015)
Identification of protein-coding regions is very difficult in genomic research. This coding regions have 3-base periodicity are named as exon. The aim of this paper is to estimate position of exon in the DNA sequence used filter approach based Fourier. For this purpose, DNA sequences of M8694 gene in human species are transformed to numeric sequences by EIIP mapping technique. Time frequency domain of numeric DNA sequences is obtained by Fourier method and 3-period signal is filtered using antinotch filter. Exon regions of filtered signal are defined successfully according to the specified percentile threshold.
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: DNA sequence; Exon; Antinotch filter; Fourier transform